The law relating to financial crime in the United Kingdom - Harrison, Karen, 1974-; Ryder, Nicholas (Abingdon, Oxon ; New York, NY : Routledge, Taylor & Francis Group, 2022)
Outlining the different types of financial crime and their impact, this book is a user-friendly, up-to-date guide to the regulatory processes, systems and legislation which exist in the UK. Each chapter has a similar structure and covers individual financial crimes including money laundering, terrorist financing, fraud, insider dealing, market abuse, bribery and corruption and finally tax avoidance and evasion. Offences are summarized and their extent is evaluated using national and international documents. Detailed assessments of financial institutions and regulatory bodies are made and the achievements of these institutions are analysed. Sentencing and policy options for different financial crimes are included and suggestions are made as to how criminal proceeds might be recovered. This third edition has been fully updated and includes a new chapter on corporate financial crime.
Introduction -- Money laundering -- Terrorist financing -- Fraud -- Insider dealing -- Market abuse -- Bribery and corruption -- The avoidance and evasion of tax -- Corporate financial crime -- Conclusions and recommendations.
OCLC-licensed vendor bibliographic record.
Keywords: Commercial crimes -- Law and legislation -- Great Britain; Terrorism -- Finance -- Law and legislation -- Great Britain -- Criminal provisions